Human-Centric AI: The Symbiosis of Human and Artificial Intelligence - Davor Horvatić; Tomislav Lipic (Entropy, 2021)
Well-evidenced advances of data-driven complex machine learning approaches emerging within the so-called second wave of artificial intelligence (AI) fostered the exploration of possible AI applications in various domains and aspects of human life, practices, and society [...]